Порівняльна оцінка енергетичних запасів екосистем України - Дідух, Я.П. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Впервые рассчитаны энергетические показатели запасов и прироста фитомассы, подстилки и почв для Украины в целом и различных типов ее экосистем. Сравниваются реальные и потенциальные показатели. Установлены зависимости между интенсивностью накопления и разложения энергии фитомассы. Воздействие антропогенного фактора привело к снижению энергозапасов фитомассы (33·1018 Дж) в 2,8 раза, подстилки (6·1018 Дж) — в два раза, а почв (140—155·1018 Дж) — на 20—30 % от потенциально возможных. Соотношение энергозапасов биомассы и почв составляет 1,0:4,7, что свидетельствует о высоком плодородии и энергоемкости почв Украины, а также о деградации, нарушенности биотического блока. Энергетические показатели являются эффективным способом оценки интенсивности антропогенного влияния и свидетельствуют об отношении человека к природе. На основе оценки энергоресурсов должны разрабатываться механизмы обеспечения устойчивого развития общества. Energy indicators for reservoirs and gain of phytomass, litter and soils of Ukraine in general and different types of its ecosystems have been calculated for the first time. Real and potential indicators are being compared. Correlations between intensity of phytomass accumulation and energy of its degradation have been elucidated. Influence of anthropogenic factor has lead to 2.8 times decrease of energy resources of phytomass (33-1018 J), 2 time decrease of energy resources of litter (6-1018 J), and 20-30 % decrease of potentially possible resources of soils (140-155-1018 J).
Ratio of energy resourses of biomass to soil was estimated as 1:4.7. Such a ratio indicates high fertility energy intensity of soils of Ukraine as well as degradation and disturbed state of biotic block.
Energy indicators are an effective way of evaluation of intensity of anthropogenic influence pointing out human attitude to nature. Evaluation of energy resourses should serve as base for elaboration of mechanisms providing stable sustainable development of community.